Integrated Water Capitalization Governance Underpins Village Autonomy : Tata Kelola Kapitalisasi Air Terpadu Menjadi Landasan Otonomi Desa - Rosaria Oktaviani; Gregorius Sahdan (Indonesian Journal of Innovation Studies, 2026)
General Background: Village autonomy depends on the capacity of local governments to convert natural assets into sustainable economic, social, and institutional value. Specific Background: Despite abundant springs, Ponggok previously experienced high poverty because its water resources were primarily used for domestic and agricultural purposes without organized productive management. Knowledge Gap: Limited research integrates governing perspectives, common-pool resource theory, and water capitalization to explain how collective natural assets support multidimensional village autonomy. Aims: This study analyzes the governance process of water resource capitalization and its contribution to economic, social, and administrative independence. Results: A descriptive qualitative design employed in-depth interviews, participatory observation, documentary analysis, and source, technique, and time triangulation. Capitalization began with a leadership-driven paradigm shift and the establishment of BUMDes Tirta Mandiri, supported by Pokdarwis Wanua Tirta, academic collaboration, private-sector partnerships, and active community participation. Water resources were diversified into tourism, agriculture, fisheries, and commercial partnerships. In 2025, Umbul Besuki generated Rp2.80 billion and Umbul Sigedang-Kapilaler generated Rp3.335 billion, while PT Tirta Investama contributed Rp1.196 billion to Village Original Revenue. These activities created employment, expanded local enterprises, reduced outward labor migration, and strengthened professional village institutions. Novelty: The study integrates collective-resource governance, institutional capitalization, and three dimensions of autonomy within one village-based framework. Implications: Sustainable local development requires visionary leadership, responsive institutions, equitable benefit distribution, inclusive participation, strategic partnerships, and continuous ecological protection. Highlights: BUMDes, tourism groups, universities, businesses, and residents formed a coordinated management structure. Two tourism units generated combined revenue exceeding Rp6.13 billion during 2025. Product diversification created local employment, supported household enterprises, and reduced labor migration. Keywords: Governing, Water Resource Capitalization, Village Autonomy, Common-Pool Resources